2022
DOI: 10.3390/ma15124134
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Magnesium Phosphate Cement-Based Fire Retardant Coating for Steel

Abstract: Magnesium phosphate cement (MPC) is a potential inorganic binder for steel coating due to setting and hardening rapidly, and bonding tightly with steel. NH4H2PO4-based MPC as a fire-retardant coating for steel was investigated in this work. MPC coatings were prepared from MPC paste and MPC mortar with expanded vermiculite (EV). The physical-mechanical properties and fireproof performance of MPC coatings were investigated in detail. An infrared thermal imager was employed to collect the temperature distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, the most rational, effective, and inexpensive method of protection is the application of coatings [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. It is possible to use a paintwork material [13,19,30] (including those with additives of nanoparticles [25,[31][32][33][34][35][36][37][38] and inhibitors [13,14,20,[39][40][41][42][43][44][45][46][47]) and zinc coating to protect the material against its intensive destruction [48].…”
Section: Introductionmentioning
confidence: 99%
“…However, the most rational, effective, and inexpensive method of protection is the application of coatings [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. It is possible to use a paintwork material [13,19,30] (including those with additives of nanoparticles [25,[31][32][33][34][35][36][37][38] and inhibitors [13,14,20,[39][40][41][42][43][44][45][46][47]) and zinc coating to protect the material against its intensive destruction [48].…”
Section: Introductionmentioning
confidence: 99%
“…These cracks enlarge with time and can cause entire sections of the spray to fail (Jaya Kumar et al. , 2022; Dai et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…When excessively large amounts are used, the insulating properties of the spray can deteriorate, and microcracks can form immediately after application of the spray. These cracks enlarge with time and can cause entire sections of the spray to fail (Jaya Kumar et al, 2022;Dai et al, 2022).…”
mentioning
confidence: 99%
“…Vijin et al [20] studied the ability of magnesium phosphate cement (MPC) coating to protect steel structures and found that no MPC coating peeled off during 45 min of burning under the flame. Dai et al [21] prepared a magnesium phosphate cement coating by mixing it with expanded vermiculite to study the physical and mechanical properties and fire performance of MPC coating. It was found that when the MPC coating thickness reached 10 mm, its fire performance met the fire resistance requirements of steel structures.…”
Section: Introductionmentioning
confidence: 99%